RISET KOMUNIKASI ORGANISASI : DALAM PERSPEKTIF INTERPRETIF DAN KRITIS - Murwani, Endah (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2006)
In the two decades, a growing number of researchers have used qualitative methods to study various aspects of organizational communication.  In  this  article,   we  examine  issues  and  challenges related to critique in qualitative research. Study of organizational communication, critical theory is concerned with the· oppressive dimensions  of corporate capitalism. These dimensions  include hegemonic   "deep-structures"  and   identities   that   are   reproducedthrough language and interaction.